Dedicated lanes, tolls and ITS technology - Robin Lindsey (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
The merits of separating cars and trucks have long been debated. Potential advantages include smoother traffic flows, lower accident rates, improved air quality and reduced maintenance and road infrastructure costs. Large trucks are often banned from urban roads and restricted to certain lanes on many highways but there are no dedicated truck facilities. However, truck-only lanes and truck tollways are now being actively studied. Tolls on cars and trucks are also becoming increasingly common and could be used to distribute car and truck traffic over road networks more efficiently. This paper reviews the potential benefits from separating cars and trucks onto different lanes or roads while treating road infrastructure as given. U.S. studies of mixed traffic operations, lane restrictions and differential speed limits do not provide consistent evidence whether separating cars and trucks either facilitates traffic flows or reduces accident rates. Analysis with an economic model reveals that the potential benefits depend on the relative volumes of cars and trucks, capacity indivisibilities and the impedance and safety hazard that each vehicle type imposes. Differentiated tolls can support efficient allocations of cars and trucks between lanes. Lane access restrictions are much more limited in effectiveness. Toll lanes that are dedicated to either cars or trucks are a potentially attractive hybrid policy. Intelligent Transportation Systems (ITS) technology can help to improve safety and travel time reliability, and help drivers select between tolled and untolled routes.
Keywords: 330